(untitled) (Research, Society and Development, 2020)
This text systematizes one part of a research bound to the Programa de Mestrado Profissional em Educação Básica [Program of Professional Master in Basic Education] (PPGEB) from Universidade Alto Vale do Rio do Peixe (UNIARP), whose purpose was to analyse the contributions of the Programa de Formação-Ação em Escolas Criativas [Program of Formation-Action in Creative Schools] towards a new meaning of the teachers pedagogical practices of the Escola Municipal de Educação Básica Gleidis Rodrigues [Gleidis Rodrigues Basic Education City School], in Timbó Grande (Santa Catarina), by means of the students’ perceptions of the first years of the Ensino Fundamental [Elementary School] about the reflexes upon the reading activities, textual production and interpretation. Methodologically, the study is featured by a research-action, anchored by a qualitative approach. The data collection was done by means of an interview applied to 12 students of the first years of the Ensino Fundamental [Elementary School]. The results highlighted the influence of the proposal in building the transdisciplinary possibilities, identified on the records about the mobilization of knowledge which was not covered within the Ensino Fundamental [Elementary School] syllabus, within the amplification of knowledge on the local reality and in the binding of field lessons with the the reading practices, textual production and interpretation.